Barriers to mental health service utilisation among medical students in Saudi Arabia - Alsalman, Zaenb; Shafey, Marwa Mahmoud; Al-Khofi, Asma; Alessa, Jumana; Bukhamsin, Raghad; Bokhuwah, May; Aljumaiah, Ryhana; Al-makhaitah, Noura; Almaslami, Maryam (Frontiers in Public Health, 2024)
Introduction Medical students experience high levels of stress, often due to academic demands, which can adversely affect their mental health. However, they frequently hesitate to seek and underutilise available mental health services. This study aimed to assess the perceived need for mental health services and identify the barriers to seeking help among undergraduate medical students. Materials and methods This cross-sectional study recruited 480 undergraduate medical students from two main universities in the Eastern Province of Saudi Arabia. Data were collected through an online, self-administered questionnaire that encompassed sections on sociodemographic details, the Patient Health Questionnaire (PHQ-9), perceptions about the necessity for professional mental health care, service utilisation over the past year, and the Barriers to Access to Care Evaluation (BACE-III). Results The study found that 33.6% of the participants showed signs of depression. Even though 42.5% expressed a perceived need for mental health services, only 16.2% actually utilised these services in the previous 12 months. In terms of barriers, attitudinal-related barriers received the highest mean score, followed by stigma- and instrumental-related barriers. Notably, students who had previously experienced academic failure and those who had sought mental health services were more inclined to report stigma- and instrumental-related barriers. Conclusion Mental health challenges are notably prevalent among undergraduate medical students. Although there is a significant perceived need for professional mental health intervention, the actual utilisation rate remains low. The primary obstacles to seeking assistance are attitudinal and stigma-related barriers.